Retained knife blade: an unusual cause for headache following massive alcohol intake. Issue 2 (26th January 2006) - Lesieur, O; Verrier, V; Lequeux, B; Lempereur, M; Picquenot, E
Abstract : Massive alcohol intake usually resolves in a banal headache. We report a case of a patient presenting with acute alcohol intoxication in which the ensuing "hangover" was due to a knife blade deeply retained in the brain parenchyma. This case underlines the unpredictability of retained foreign bodies without a high level of suspicion and a detailed description of the circumstances of admission.